Sekcja Bokserska zebranie reorganizacyjne. (Tczew : [s.n.], 1947)
Afisz inf. o zebraniu 25.09.1947 r. klub K.K.S. "Unia".
Keywords: Boks -- Polska -- Tczew -- 1945-1970 -- druki ulotne; Tczew (Polska) -- 1945-1970 -- druki ulotne